2015
DOI: 10.5539/gjhs.v7n4p399
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine-Prilocaine Cream as Analgesia for IUD Insertion: A Prospective, Randomized, Controlled, Triple Blinded Study

Abstract: Introduction:Copper IUD is a long term and reversible contraception which equals tubal ligation in terms of sterilization. One of the barriers to using this contraception method is the fear and the pain associated with its insertion. Eutectic mixture of local anesthetics (EMLA) 5% is a local anesthetic that contains 25 mg lidocaine and 25 mg of prilocaine per gram. Application of topical analgesic cream to the cervix for laser surgery, hysteroscopy and hysterosalpingography is knownAims:this study aimed to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 16 publications
2
27
2
Order By: Relevance
“…In many of the clinics, ibuprofen and preparations, non-steroidal drugs, anti-inflammatory drugs, and cervical emollient drugs (misoprostol) and a topical anesthetics to alleviate the pain during the IUD insertion are used [5] [7] [10]. One a local anesthetic drugs is EMLA cream 5% that each gram of this cream contains lidocaine 25 mg and prilocaine 25 mg [12]. The analgesics application of this cream is topical on the cervix made to perform laser surgery procedures, hysteroscopy, and Hysterosalpingography [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…In many of the clinics, ibuprofen and preparations, non-steroidal drugs, anti-inflammatory drugs, and cervical emollient drugs (misoprostol) and a topical anesthetics to alleviate the pain during the IUD insertion are used [5] [7] [10]. One a local anesthetic drugs is EMLA cream 5% that each gram of this cream contains lidocaine 25 mg and prilocaine 25 mg [12]. The analgesics application of this cream is topical on the cervix made to perform laser surgery procedures, hysteroscopy, and Hysterosalpingography [13] [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions included lidocaine gel, lidocaine‐prilocaine (LP) cream, lidocaine intracervical block, lidocaine infusion, and nitroglycerin gel. Nine RCTs reported lower VAS pain scores in the treatment group compared with the control/placebo group …”
Section: Resultsmentioning
confidence: 99%
“…Although 12 RCTs were identified as being at low risk of bias within these categories, when looking at the potential for “other sources” of bias, all were seen as being at high risk due to a number of factors: they offered other analgesics besides the study drugs, recruited women who were looking for IUC placement and, in some cases, there was overlap in the VAS pain scores between treatment and placebo groups or the VAS pain scores in both groups were low (<4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Nevertheless, there are studies being published which show that topical use of different formulations involving high concentrations of lidocaine mitigates IUD insertion pain at every step of the procedure. [24][25][26] It was shown that paracervical blockage in injectable applications of local anesthetics mitigates IUD application pain but intracervical injectival application is not effective on the pain. 3,27 In consideration of injection's own pain and possible adverse reactions, topical application of local anesthetics is regarded as being more advisable.…”
Section: Discussionmentioning
confidence: 99%